Use of weeds as traditional vegetables in Shurugwi District, Zimbabwe - Maroyi, Alfred (BioMed Central, 2013)
BACKGROUND: Most agricultural weeds are usually regarded as undesirable and targeted for eradication. However, weeds are useful to human beings as food and traditional medicines. Few studies have been done to document the uses of weeds as traditional vegetables. This study was therefore, done to document indigenous knowledge related to the diversity and use of agricultural weeds as traditional vegetables in Shurugwi District, Zimbabwe, emphasizing their role in food security and livelihoods of the local people. MATERIALS AND METHODS: Semi-structured interviews, observation and guided field walks with 147 participants were employed between December 2011 and January 2012 to obtain ethnobotanical data on the use of edible weeds as traditional vegetables. Based on ethnobotanical information provided by the participants, botanical specimens were collected, numbered, pressed and dried for identification. RESULTS: A total of 21 edible weeds belonging to 11 families and 15 genera, mostly from Amaranthaceae (19%), Asteraceae and Tiliaceae (14.3%), Capparaceae, Cucurbitaceae and Solanaceae (9.5% each) were identified. Of the documented edible weeds, 52.4% are indigenous while 47.6% are exotic to Zimbabwe; either semi-cultivated or growing naturally as agricultural weeds in farmlands, fallow land and home gardens. Among the main uses of edible weeds were leafy vegetables (81%), followed by edible fruits (19%), edible corms (9.5%), edible flowers and seeds (4.8% each). The most important edible weeds were Cleome gynandra, cited by 93.9% of the participants, Cucumis metuliferus (90.5%), Cucumis anguria (87.8%), Corchorus tridens (50.3%) and Amaranthus hybridus (39.5%). All edible weeds were available during rainy and harvest period with Cleome gynandra, Corchorus tridens, Cucumis anguria, Cucumis metuliferus and Moringa oleifera also available during the dry season, enabling households to obtain food outputs in different times of the year. The importance of edible weeds for local livelihoods was ubiquitously perceived, with all participants reporting their contribution towards food security and nutrition. CONCLUSION: The present study confirm findings from similar studies conducted elsewhere that rural households engage in harvesting of wild edible vegetables and other non-timber forest products (NTFPs) as a survival strategy. Based on their potential nutritional and medicinal value, edible weeds could contribute in a major way to food security, basic primary health care and balanced diets of rural households and possibly urban households as well.